Kekuatan Hukum Akta Kelahiran Anak Luar Kawin - Dewa Ayu Gita Trisna Dewi; Desak Gde Dwi Arini; Ni Gusti Ketut Sri Astiti (Fakultas Hukum, Universitas Warmadewa, 2021)
Indonesia is a legal state with the concept of an Indonesian legal state where law is an idealized goal together in the dynamics of state life. So in living life, humans have the right to marry and continue a legal marriage and the goal is to continue the offspring. However, not all children are born from legal marriages. These unlucky children are known by law as illegitimate children. The purpose of this study is to analyze the regulation of children out of wedlock according to the Civil Code and customary law and the legal force of birth certificates for children out of wedlock. This type of research is normative legal research with a conceptual approach. Legal sources are secondary, primary and tertiary sources of law which are then analyzed systematically. The results of the study revealed that the regulation of children out of wedlock was regulated through written and unwritten awig-awig because awig-awig was a guide for traditional villages in running their government. The child's acknowledgment can be stated in a Notary Deed or in a Birth Certificate or a Deed made by a civil registry official or it is also possible with the marriage certificate itself. Because, birth certificates are very important for children because it is a form of state recognition regarding the citizenship status, civil status of the child.